KEBIJAKAN RENCANA TATA RUANG WILAYAH PERBATASAN KOTA DENGAN KABUPATEN - Budiman Widodo (Universitas Riau, 2013)
Spatial Planning Policy Border Town District. This research ismotivated complete lack of city and county goverments in addressing issuesof suburban areas. This study aims to determine how the government's policyon spatial planning in regulating land use in the border area. Subjects wereinformants of the bureaucrats, businessmen, and the society who were takento the snowball sampling method. Data was collected with qualitativemethods through in-depth interview, observation and documentation.Analysis of the data using an interactive method . The results showed that thespatial planning policy of cities and counties to regulate land use in the areaof border policy has not been effective because of spatial plans of each cityand county to be partial and can not anticipate changes in the dynamics ofrapid economic, social, transport and the environment. The implication of thisstudy is that by letting the policy approach (not to do), is still relevant incertain circumstances, but necessary for the long-term future spatial policywhich can regulate border issues both regions .Keywords: government policy, spatial planning, policy impact, socialconflict .